M. Arizmendi, M. López Suárez, A. Suárez Miramón: Análisis de obras literarios. El autor y su contexto, Madrid, Síntesis, 1996, 493 pp. - Martínez-peñuela, Ana (Cuadernos de Filología Italiana, 1997)
Sin resumen